P18-51 Advancing in vitro Developmental Neurotoxicity (DNT) screening: Expanding the biological coverage of the DNT in vitro battery (IVB) by integration of glial cell-related endpoints - A.S. Cheruvil lilikumar; E. Zühr; R. Guzzo; E. Fritsche; K. Koch (Toxicology Letters, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

OS04-05 Addressing uncertainties in the DNT in vitro battery (DNT IVB) by incorporating glial models and increasing human relevance - K. Koch; E. Zühr; K. Bartmann; R. Guzzo; A.S. Cheruvil Lilikumar; L. Stark; I. Egger; O. Myhre; E. Fritsche (Toxicology Letters, 2024)

Development of an analytical platform for the affinity screening of natural extracts by SEC-MS towards PPARα and PPARγ receptors - G. De Soricellis; F. Rinaldi; S. Tengattini; C. Temporini; S. Negri; D. Capelli; R. Montanari; H. Cena; S. Salerno; G. Massolini; F. Guzzo; E. Calleri (Analytica Chimica Acta, 2024)

Potential of native palm species in Northeast Brazil as hosts for the invasive mite Raoiella indica (Acari: Tenuipalpidae) - I. V. Souza; R. P. Lyra-Lemos; E. C. Guzzo (Experimental and Applied Acarology, 2020)

Lapidary production in the eastern Caribbean: a typo-technological and microwear study of ornaments from the site of Pearls, Grenada - Catarina Guzzo Falci; Alice C. S. Knaf; Annelou van Gijn; Gareth R. Davies; Corinne L. Hofman (Archaeological and Anthropological Sciences, 2020)
The present paper examines bodily ornaments made of semiprecious lithic materials from the site of Pearls on the island of Grenada. The site was an important node in long-distance interaction networks at play between circum-Caribbean communities during the first centuries of the Common Era. Pearls was an amethyst bead-making workshop and a gateway to South America, from where certain lapidary raw materials likely originated. The importance of the site for regional archaeology and local stakeholders cannot be overstated. However, it has undergone severe destruction and looting over the decades. Here, we present a study of a private collection of ornaments from Pearls, which combines raw material identification, typo-technological analysis and microwear analysis. We identify great diversity in lithologies and in techniques adapted to their working properties. Multiple abrasive techniques for sawing, grinding, polishing and carving are identified. Furthermore, the use of ornaments is examined for the first time. Finally, we contrast our dataset to other Antillean sites and propose management patterns for each raw material. Our approach ultimately provides new insights on ornament making at Pearls and on its role in regional networks.

Homogenization of freshwater lakes: Recent compositional shifts in fish communities are explained by gamefish movement and not climate change - Kevin Cazelles; Timothy Bartley; Matthew M. Guzzo; Marie‐Hélène Brice; Andrew S. MacDougall; Joseph R. Bennett; Ellen H. Esch; Taku Kadoya; Jocelyn Kelly; Shin‐ichiro Matsuzaki; Karin A. Nilsson; Kevin S. McCann (Global Change Biology, 2019)
Globally, lake fish communities are being subjected to a range of scale‐dependent anthropogenic pressures, from climate change to eutrophication, and from overexploitation to species introductions. As a consequence, the composition of these communities is being reshuffled, in most cases leading to a surge in taxonomic similarity at the regional scale termed homogenization. The drivers of homogenization remain unclear, which may be a reflection of interactions between various environmental changes. In this study, we investigate two potential drivers of the recent changes in the composition of freshwater fish communities: recreational fishing and climate change. Our results, derived from 524 lakes of Ontario, Canada sampled in two periods (1965–1982 and 2008–2012), demonstrate that the main contributors to homogenization are the dispersal of gamefish species, most of which are large predators. Alternative explanations relating to lake habitat (e.g., area, phosphorus) or variations in climate have limited explanatory power. Our analysis suggests that human‐assisted migration is the primary driver of the observed compositional shifts, homogenizing freshwater fish community among Ontario lakes and generating food webs dominated by gamefish species.

Gamma-rays and heat-treatment conversions of point defects in massive rose quartz from the Borborema Pegmatite Province, Northeast Brazil - Pedro L. Guzzo; Sandra B. Barreto; Milena R. Miranda; Raysa S. G. Gonzaga; Sandra A. Casals (Physics and Chemistry of Minerals, 2017)

Thymoquinone-induced Neu4 sialidase activates NFκB in macrophage cells and pro-inflammatory cytokines in vivo - Trisha M. Finlay; Samar Abdulkhalek; Alanna Gilmour; Christina Guzzo; Preethi Jayanth; Schammim Ray Amith; Katrina Gee; Rudi Beyaert; Myron R. Szewczuk (Glycoconjugate Journal, 2010)

Thymoquinone from nutraceutical black cumin oil activates Neu4 sialidase in live macrophage, dendritic, and normal and type I sialidosis human fibroblast cells via GPCR Gαi proteins and matrix metalloproteinase-9 - Trisha M. Finlay; Preethi Jayanth; Schammim Ray Amith; Alanna Gilmour; Christina Guzzo; Katrina Gee; Rudi Beyaert; Myron R. Szewczuk (Glycoconjugate Journal, 2010)

Point defects and pre-dose requirements for sensitization of the 300°C TL peak in natural quartz - Pedro L. Guzzo; Helen J. Khoury; Milena R. Miranda; Sandra B. Barreto; Armando H. Shinohara (Physics and Chemistry of Minerals, 2009)